Mechanical response of layered titanate nanowires. Issue 11 (1st August 2020) - Rossi, L.; Foschia, R.; Glushkova, A.; Forró, L.; Horváth, E.
Abstract: The mechanical response of individual titanate nanowires (H2 Ti3 O7 ), synthesized in an upscaled production (kg/month) was investigated by means of an Atomic Force Microscope (AFM) in nanomechanical spectroscopic mode. Because of their layered structure, besides the Young's modulus (E) of 66.7 ± 25 GPa, an important contribution to the mechanical response was identified as coming from the low shear modulus (G) of 1.5 ± 0.8 GPa between the layers. The mechanical energy loss due to shear is at the origin of the material's fatigue, during which the individual titanate layers crack gradually, until the final failure of the structure. The high-temperature treatment at 800 °C transforms the material into anatase (TiO2 ) nanowires, which have a considerably higher elastic modulus.